2021
DOI: 10.4062/biomolther.2021.120
|View full text |Cite
|
Sign up to set email alerts
|

A New Murine Liver Fibrosis Model Induced by Polyhexamethylene Guanidine-Phosphate

Abstract: Liver fibrosis is part of the wound healing process to help the liver recover from the injuries caused by various liver-damaging insults. However, liver fibrosis often progresses to life-threatening cirrhosis and hepatocellular carcinoma. To overcome the limitations of current in vivo liver fibrosis models for studying the pathophysiology of liver fibrosis and establishing effective treatment strategies, we developed a new mouse model of liver fibrosis using polyhexamethylene guanidine phosphate (PHMG-p), a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
“… 89 Furthermore, PHMG was found to cause liver fibrosis in male rats in one study. 90 Previously, Leem and Chung 132 estimated that PHMG could have effects not only on the lungs but also on various other organs due to increases in reactive oxygen species and changes in the composition of T lymphocytes. Exposure to PHMG and CMIT/MIT was linked to cardiotoxicity in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Farnesyl pyrophosphate analogs with azido, aldehyde, and alkynes have also been reported to be transferred by PFTase. PFTase also acts as a prenyltransferase, adding isoprenoid groups to Cys residues in the CaaX recognition tag, where “a” is an aliphatic amino acid and “X” is the amino acid specific to a particular isoprenyltransferase [49] . This technology has been used to produce regioselective and homogeneous ADCs.…”
Section: Overview Of Enzymatic Conjugation In Adcsmentioning
confidence: 99%
“…PFTase also acts as a prenyltransferase, adding isoprenoid groups to Cys residues in the CaaX recognition tag, where "a" is an aliphatic amino acid and "X" is the amino acid specific to a particular isoprenyltransferase. [49] This technology has been used to produce regioselective and homogeneous ADCs. ADCs made by combining prenylation conjugation technology with a payload bearing a β-glucuronidase cleavage linker have shown high stability in preclinical evaluations.…”
Section: Protein Farnesyltransferasementioning
confidence: 99%
“…Liver : The causality of PHMG exposure and liver disease remained questionable in the past ( Lachenmeier, 2014 [R]; Lachenmeier et al, 2012 [r]; Solodun et al, 2011 [E]). However, a 5-week study in mice showed that PHMG causes diffuse fibrotic lesions in the liver and that it affects several pathways associated with human liver fibrosis ( Kim et al, 2022 ) [E].…”
Section: Guanidinesmentioning
confidence: 99%